Strategi Pengembangan “Wisata Agro Kebun Kaligua” PT Perkebunan Nusantara IX Indonesia - Hendro Prawiro; Bambang Dwiloka; Frida Purwanti (Gemawisata: Jurnal Ilmiah Pariwisata, 2020)
This study aims to identify the characteristics and perceptions of tourists, internal and external factors that affect the development of the company and develop the company's development strategy. Strategy of Agro Tourism Development Kaligua was prepared based on descriptive analysis with analytical tool that is: descriptive analysis to identify tourists' characteristic and perception, SWOT analysis to identify internal and external factors influencing company development, and AHP to develop company development strategy. The result of identification of tourist characteristic that visited at Agro Tourism Kaligua Garden that is average tourist is dominated by young man with age <35 years amount 76% with income less than Rp 2.000.000 some 58%. Tourists judge Agro Tourism Kaligua has beautiful attractions, good facilities and positive institutional and promotional services, but affordability is still negative due to poor road quality and road guidance. Result of SWOT analysis, Agro Tourism Kaligua has five strength factor with score 1.89, five weakness factor with score 1,3, five chance factor with score 1,88, and five threat factor with score 1,21. Having the position of corporate strategy in quadrant I with coordinates X of 0.57 and Y of 0.67 is on the SO position in the form of aggressive strategy that can create Agro Tourism Kaligua to use the strength and chances in determining company policy and develop development strategies to achieve the target profit in the future. The formulation of tourism development strategy of Kaligua Garden Estate is optimizing marketing, improving the quality of tourism, and developing tourism product. In general, Agro Tourism development strategy applied is the best with the status quo and followed by expansionary strategy. The main priority that must be done is to maintain the quality of tourism, especially improving the quality of service so that tourists can feel satisfied and comfortable tour at Agro Tourism Kebun Kaligua.